Pengaruh Model Discovery Learning Berbantuan Photomath Terhadap Kemampuan Pemecahan Masalah Matematis Siswa SMP (Lembag, 2026)
Being able to solve problems is a key part of learning math. Many students still haven't fully understood this skill, especially when it comes to Statistics. This happens because the teaching methods haven't fully supported students in being more involved, and technology isn't being used as effectively as it could be in the lessons. So, this study was done to look at how using the Discovery Learning method along with the Photomath app affects students' ability to solve math problems. The study took place at SMPN 2 Gondangwetan during the 2024/2025 school year. It used a quasi-experimental method with a nonequivalent control group setup. The study included two groups of eighth-grade students, with each group having 30 students. Class VIII-A was the control group, and Class VIII-B was the experimental group. Data was gathered using written exams given before and after the teaching program. The pretests showed that the data followed a normal distribution but had unequal variances, so the Mann–Whitney U test was chosen to check the hypothesis. The analysis found a significance level of 0.003, which is below 0.05, showing there was a true difference between the two groups. The biggest progress was seen in the experimental group, especially in the areas of evaluating and making conclusions, which went up from 3% to 81%. So, it's clear that using the Discovery Learning model along with the Photomath app has a big positive impact on helping students improve their math problem-solving skills.